CENTELLA ASIATICA EXTRACT EFFECT ON POSTOPERATIVE WOUND HEALING - Iskandar, Elza; Theodorus, Theodorus; Tribowo, Anang; Erna, Riani; Syakirah, Fatimah (International Islamic Medicine Forum, 2021)
Wound healing is a complex process that is divided into four phases, namely the hemostasis, inflammation, proliferation, and tissue remodeling phase. Centella asiatica is a widely used and very popular traditional plant in the field of health for a long time. Various in vitro and in vivo studies have proven the efficacy of Centella asiatica extract in the wound healing process. This literature review uses literature search methods from Pubmed, Science Direct, and Cochrane Library with keywords Centella asiatica, wound healing, surgery. This study aims to study the effects of Centella asiatica extract on postoperative wound healing.